Polygamy or subdioecy? The impact of diallelic self-incompatibility on the sexual system in Fraxinus excelsior (Oleaceae). Issue 1873 (21st February 2018) - Saumitou-Laprade, Pierre; Vernet, Philippe; Dowkiw, Arnaud; Bertrand, Sylvain; Billiard, Sylvain; Albert, Béatrice; Gouyon, Pierre-Henri; Dufay, Mathilde
Abstract : How flowering plants have recurrently evolved from hermaphroditism to separate sexes (dioecy) is a central question in evolutionary biology. Here, we investigate whether diallelic self-incompatibility (DSI) is associated with sexual specialization in the polygamous common ash ( Fraxinus excelsior ), which would ultimately facilitate the evolution towards dioecy. Using interspecific crosses, we provide evidence of strong relationships between the DSI system and sexual phenotype. The reproductive system in F. excelsior that was previously viewed as polygamy (co-occurrence of unisexuals and hermaphrodites with varying degrees of allocation to the male and female functions) and thus appears to actually behave as a subdioecious system. Hermaphrodites and females belong to one SI group and functionally reproduce as females, whereas males and male-biased hermaphrodites belong to the other SI group and are functionally males. Our results offer an alternative mechanism for the evolution of sexual specialization in flowering plants.